«Vi er aldri syke, derfor holder vi oss friske og eldes ikke […]»: Knut Hamsun og Pauline fra Polden i et helsemessig perspektiv - Torrissen, Wenche (Nordlit, 2016)
Can we learn anything about well-being and what it is that constitutes the ‘mystery’ of health by reading Knut Hamsun’s novels? This article argues that Knut Hamsun in his description of the character Pauline Andreassen in the August trilogy (1927–1933), illustrates central elements of what modern radical philosophers (Ivan Illich, Hans-Georg Gadamer, and Aaron Antonovsky) understand about good health and well-being, namely: the ability to adapt to a society, the ability to establish a life based on one’s own interests and possibilities, and the ability to cope with different emotional losses and challenges in life. This article also gives a brief introduction to Hamsun’s harsh criticism of bio-medical institutions and the way they tend to medicalize society. As a contribution to the health/humanities debates, this article also investigates how the humanities can enhance our knowledge and understanding of health and well-being.